Factors affecting sustainable marketing on small business in the northern region of Iraq - Biro Munaf, Mikaeel; Akbay, Cuma (Technium Social Sciences Journal, 2022)
Sustainable marketing is the promotion of environmental and socially responsible products, practices, and brand values. The main objective of this study is to investigate the factors affecting sustainable marketing on small business in the Northern-Iraq. The sample of the study includes all the workers in small businesses. The targeted sample size of the study is 400 workers who are selected randomly. A poll was planned and used to record data based on a Likert scale (five scores) incorporates the workers' characteristics regarding the sustainability factors. I evaluated the pre-prepared questions with the workers and managers of small business face-to-face. And also this questionnaire in the 2017 year collected. The data were analyzed with SPSS programs by utilizing methods containing descriptive statistics, Chi-square test. The outcomes demonstrated that the effective factors that sustainable marketing the workers in the small business are in accordance with the multidimensional structure of mental and sociological issues and perceiving every one of these undertakings and acing them and proposing and submitting arrangements make the errands and duties of the managers more difficult. Research included “Gender”, “Education”, “Extreme poverty “Attitudes and beliefs”, “Government intuition " and “Low”, a significant role insupportable promoting an independent company.